Good news or bad? The shifting points of intersection in the game of elite sport development in NZ - Ryan, I; Martin, S (University of Gothenburg, 2011)
Critical and postmodern approaches remain on the fringes of sport management research (Skinner and Edwards, 2005). The purpose of the study proposed in this paper is to broaden the scope and conceptual complexity of a topic that matters to New Zealand (NZ) and globally; elite sport performance. The intent is to use an intersectional approach to highlight the interplay over time between macro – societal institutions and meso - organisational factors and the impact on the work-life experiences of amateur elite athletes. The concept of intersectionality is used in women’s studies and feminist theory to understand the relationship between interrelating categories of inequality and unequal power relations (Acker, 2006; Calas and Smircich; Holvino, 2008). Different approaches to the theorization of intersectionality has stimulated a rich scholarly debate as to its strengths and weaknesses as scholars seek further understanding and explanation of the concept (eg Bilge, 2010; Dill, McLaughlin and Nieves, 2007; Holvino, 2008; McCall, 2005; Naples, 2009; Phoenix and Pattynama, 2006; Yuval-Davies, 2006). Bilge (2010) summaries this debate as one that exists on two levels: level one, discussions on theories and methodologies and level two, praxis or the application of intersectional knowledge to advance equality. Considering the scholarly debate, this paper represents our initial thinking on how to conceptualize an intersectional research project: what to include and what to exclude or see as peripheral to the analysis (Naples, 2009).